PELATIHAN PARENTING SKILL PADA WALI SANTRI TPQ AL IKHLAS DI ERA DIGITAL DI DUSUN BANDUNG ROWO KEDUNG SOKO KEC.PLUMPANG - Roudlotun Ni’mah; Khoirotus Silfiyah; Farida Isroani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The Digital Age is a period that cannot be separated from the rapid increase in information technology. Islamic nature and character is very valuable as a channel and barrier for children at TPQ in managing information technology in today's digital era. This is what underlies the importance of Parenting Skill Training for TPQ Al Ikhlas Santri Guardians in the Digital Era, the Islamic Digital Parenting community movement program. This program demonstrates to introduce the computerized world to guardians, and teach them to have the option of getting ready. Young people are facing the rapid advancement of innovation by applying Islamic traits to children. This Business Program aims to provide skills to prepare and provide knowledge to guardians regarding correct Islamic parenting patterns for children in old age. Departing from this problem, then, at that time, what the guardians of santri needed to do to prevent and survive the bad consequences of the computerized world was to develop Digital Resilience in children. Advanced Resilience is its capacity to control the possible risks of an internet-based world by developing virtues in young people (Shotbolt, 2016, 2017). This work should be made possible by instilling great Islamic qualities and character in young people.